Workbook for Greathouse’s Radiographic Positioning & Procedures - Greathouse, Joanne S (Thomson/Delmar Learning, 2006)
The study of radiographic positioning and procedures is one of the most difficult subject areas in the field of radiographic sciences. This workbook is an essential tool to be used with the textbook to facilitate the learning process and ease you through an intense subject area. The knowledge gained in this area of radiography is not meant solely to be memorized but must be applied. The goal of the workbook is to hone problem-solving skills that will enable you to apply what you are learning to real-world situations in the field of radiography